On spatial variation in the detectability and density of social media user protest supporters - Víctor Hugo Masías; Fernando A. Crespo R.; Pilar Navarro R.; Razan Masood; Nicole C. Krämer; H. Ulrich Hoppe (Telematics and Informatics, 2021)
Although much has been published regarding street protests on social media, few works have attempted to characterize social media users' spatial behavior in such events. The research reported here uses spatial capture-recapture methods to determine the influence of the built environment, physical proximity to protest location, and collective posting rhythm on variations in users' spatial detectability and density during a protest in Mexico City. The best-obtained model, together with explaining the spatial density of users, shows that there is high variability in the probability of detection of social media user protest supporters and that the collective posting rhythm and the day of observation are significant explanatory factors. The implication is that studies of collective spatial behavior would benefit by focussing on users' activity centres and their urban environment, rather than their physical proximity to the protest location, the latter being unable to adequately explain spatial variations in users' probability of detection and density during the protest event.
Keywords: 300; protest event; social media; posting rhythms; spatio–temporal behavior; urban environment